Constrained Efficiency in the Neoclassical Growth Model With Uninsurable Idiosyncratic Shocks - Dávila, Julio; Hong, Jay H.; Krusell, Per; Ŕıos-Rull, José-V́ıctor (Econometrica, 2012)
We investigate the welfare properties of the one-sector neoclassical growth model with uninsurable idiosyncratic shocks. We focus on the notion of constrained efficiency used in the general equilibrium literature. Our characterization of constrained efficiency uses the first-order condition of a constrained plannerâs problem. This condition highlights the margins of relevance for whether capital is too high or too low: the factor composition of income of the (consumption-) poor. Using three calibrations commonly considered in the literature, we illustrate that there can be either over- or underaccumulation of capital in steady state and that the constrained optimum may or may not be consistent with a nondegenerate long-run distribution of wealth. For the calibration that roughly matches the income and wealth distribution, the constrained inefficiency of the market outcome is rather striking: it has much too low a steady-state capital stock.